Pre-competition state and trait of anxiety level among the Malaysian Asean Para Games 2017 wheelchair athletes / Muhammad Shafiz Muhammad Sakir - Muhammad Sakir, Muhammad Shafiz (Faculty of Sports Science and Recreation, 2018)
The purpose of this study was to investigate the difference of state and trait of anxiety level between male and female Malaysian ASEAN Para Games wheelchair athletes. In addition, the researcher also to determine the relationship between state and trait of anxiety level among the Malaysian ASEAN Para Games wheelchair athletes. There are 36 wheelchair athletes were chosen via stratified sampling to participate in this study. The instrument used in this study was the State Trait Anxiety Inventory (STAI) questionnaire and demographic questionnaire. Independence T-Test was used to identify the difference, the results show that there was no significant difference of state and trait of anxiety level between male and female wheelchair athletes (p = 0.387, P = 0.904). Using Pearson Correlation to determine the relationship, the results show that there were significant differences between state and trait anxiety level (r = 0.807, p = 0.000). As a conclusion, the anxiety level of the wheelchair athletes did not depend on gender and there were positive relationships between state and trait anxiety level.